Preemptive treatment with voriconazole in lung transplant recipients. Issue 4 (25th March 2013) - Neoh, C.F.; Snell, G.I.; Levvey, B.; Kotsimbos, T.; Morrissey, C.O.; Slavin, M.A.; Stewart, K.; Kong, D.C.M.
Abstract Background Invasive fungal infection (IFI) is associated with high mortality in lung transplant (LTx) recipients. Data for voriconazole use in preemptive treatment remain scant. Method A single‐center, retrospective cohort study was conducted to investigate the efficacy and safety of voriconazole preemptive treatment for post‐LTx colonization. Results We reviewed 62 adult LTx patients, who received their first course of voriconazole prophylaxis (i.e., as preemptive treatment) between July 2003 and June 2010. Outcomes were determined at 6 and 12 months after commencing therapy. Aspergillus fumigatus (75.8%) was the most common colonizing isolate. Median duration of voriconazole prophylaxis was 85 days. At 6 months, 1 LTx patient (1.6%) had IFI, 47 (75.8%) cleared their colonizing isolate, 3 (4.8%) had persistent colonization, 7 (11.3%) had recurrent colonization, 1 (1.6%) had new colonization, 2 (3.2%) had aspergilloma, and 1 (1.6%) was clinically unstable with no culture results. Sixteen (25.8%) had died by 12 months. Ten (16.1%) had likely drug‐related hepatotoxicity. LTx patients with diabetes mellitus within 30 days before commencing prophylaxis were at higher risk of recurrent Aspergillus colonization at 6 months (P = 0.030). Chronic rejection within 30 days before prophylaxis was associated with 12‐month mortality (P = 0.007). Conclusions Voriconazole preemptive treatment resulted in low incidence of IFI and IFI‐related mortality.